(3HGfJ SYGOs - (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3HGfJ SYGO abdHi Gdjhe eJHhd eJje EKQgG de jaO ecHhd s
(3BNQgG (B:s
(3dGjhbYhG GdWYf EdG ai fMhQge heG dge Yf MjG GdehJ Jgdjd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B52 - (3U(B58s
(3GfXQgG eY eLehYI TYQjI ChdgG QLhRI aj eYGfj eKdKGJ bWQHs
(3hQO CjVkG JMJ Qbe (B" 2185(3, (B2187" s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B226s
Keywords: (3GdCOHs